Draft Annual Plan 1985-86 Vol.-III Government of Tripura - Planning Commission (Planning Commission, 1985)
Tripura is a land locked state and is dependent mainly on roads for its Communication system. So far there is hardly 20 Km length of railway line in Tripura. Improvement of road communication system therefore deserves priority for the integrated Rural development programme in Tripura.
Government of Tripura